Investment Guarantees in Gas Fields - Yassin, Dania; Hussain, Akram (Journal of Legal Sciences, 2023)
In the field of research in the investment of gas fields, this requires that we first look at the center of the contracting parties in terms of the guarantee means granted to them under the contract, which constitute a means of safety and motivation to enter as major parties in the investment project. In turn, we will discuss the minimum guarantees, which are the most important guarantees granted to each of the two parties to the contract, namely the national party and the investor.